Avaliação da eficácia de um protocolo de terapia cognitivo-comportamental em grupos para redução dos sintomas de ansiedade - Garcez, Lívia (2024)
The COVID-19 pandemic has resulted in health restrictions such as isolation/social distancing, which significantly increased anxiety symptoms in the adult population. To meet this demand, the mental health services began to offer remote care. However, little is known about the effectiveness of online psychological care in different theoretical approaches. In this context, we carried out a clinical trial randomized with 44 adults (ages between 18 and 60 years) who had anxiety symptoms. Participants were divided into two groups: one group received a brief intervention based on Cognitive-Behavioral in Groups through online sessions, while the other group received a psychoeducational intervention (control group). We use instruments such as the Demographic Data Questionnaire, Clinical Interview based on the Diagnostic Criteria for Anxiety Disorder Generalized from the DSM-5-TR and the Beck Anxiety Inventory (BAI), all applied online. The interventions took place in five meetings each session lasting 60 minutes. After applying the instruments, we analyzed the participants' demographic data and pre- and post-intervention scores in both groups. We calculated the delta scores of the outcome (fifth week scores - baseline assessment scores) for each intervention group. The TCCG protocol demonstrated equivalent results to other therapeutic procedures to reduce anxiety symptoms.